1997
DOI: 10.1007/s002770050288
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for capillary leakage syndrome after bone marrow transplantation

Abstract: Age, hematopoietic growth factors, cyclosporin A, mode of bone marrow transplantation (BMT) (autologous, allogeneic-related, unrelated), and underlying disease were assessed as potential risk factors for capillary leakage syndrome (CLS) in 96 patients after BMT. CLS was defined as unexplained weight gain of > 3% within 24 h and nonresponsiveness to furosemide. CLS occurred in 9/21 patients after unrelated compared with 2/33 after allogeneic-related BMT (p = 0.0017) for hematopoietic disorders (n = 54) and in 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
56
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 13 publications
(12 reference statements)
0
56
0
Order By: Relevance
“…Lee et al 1 found that sepsis in the first week of neutropenia decreased the incidence of this syndrome and that the incidence was significantly higher after 1989 (following the introduction of aggressive prophylactic antibiotic therapy). In the Nurnberger series, 6 CLS occurred more frequently among recipients of unrelated donor BMT than matched related BMT and in allogeneic more than autologous BMT recipients with solid tumors.…”
Section: Autologous Stem Cell Transplantationmentioning
confidence: 96%
See 1 more Smart Citation
“…Lee et al 1 found that sepsis in the first week of neutropenia decreased the incidence of this syndrome and that the incidence was significantly higher after 1989 (following the introduction of aggressive prophylactic antibiotic therapy). In the Nurnberger series, 6 CLS occurred more frequently among recipients of unrelated donor BMT than matched related BMT and in allogeneic more than autologous BMT recipients with solid tumors.…”
Section: Autologous Stem Cell Transplantationmentioning
confidence: 96%
“…The term engraftment syndrome (ES) has, therefore, been most widely applied to describe this clinical entity. [1][2][3][4] Other terms that have been used to describe this syndrome have included capillary leak syndrome (CLS), 5,6 reflecting the clinical manifestations of diffusely increased capillary permeability, and autoaggression syndrome, signifying a possible immunological component in the autologous HCST setting. 7 In its most extreme form, in which profound hemodynamic collapse and multi-organ system failure may develop, the term aseptic shock syndrome has been applied.…”
mentioning
confidence: 99%
“…Early reports of capillary leak syndrome after allotransplants identified clinical outcomes used to diagnose ES. Nurberger et al 5 reported capillary leak syndome (unexplained weight gain 43% of baseline weight within 24 h of engraftment and unresponsive to furosemide therapy) was more common after allo-vs autotransplants. In contrast, Cahill et al 4 reported similar rates.…”
Section: Engraftment Syndromementioning
confidence: 99%
“…[1][2][3] Most data suggest ES results from a proinflammatory state caused by release of diverse cytokines and other mediators of inflammation. ES was previously referred to as capillary leak syndrome, 4,5 autoaggression syndrome (after autotransplants) 6,7 and (when severe) aseptic shock syndrome. 8 ES is described after umbilical cord blood transplants and auto-, allo-and syngeneic-transplants of blood cells and BM cells.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have also addressed the impact of risk factors on post-BMT complications. [6][7][8][9][10] During the past decades we have improved our ability to prevent and/or treat such complications, and transplantrelated mortality (TRM) has been considerably reduced 11 and delayed: in our HLA-identical sibling program TRM was 39% before 1990 (385 patients) and occurred at a median interval of 48 days from BMT (range 1-1230); TRM is currently 17% (333 patients) with a median interval from transplant of 103 days (range 8-1419) (P Ͻ 0.00001) (unpublished). Very few patients die before day +7: the 10th percentile is currently day 30, and the 75th percentile is day 202.…”
mentioning
confidence: 99%